Investigating the Consumer Implications of Artificial Emotional Intelligence (AEI) in the context of Digital Banking in South Africa - Reddy, Sanussha (University of the Witwatersrand, Johannesburg, 2024)
A revolution in human-computer interaction has been brought about by the swift developments of artificial intelligence (AI), especially following the emergence of artificial emotional intelligence (AEI). The integration of AEI in the South African digital banking industry was investigated in this master's thesis, along with the potential and limitations it represented. The study used a quantitative research technique to collect data from Gauteng region residents who use digital banking. Surveys were used to evaluate user experience, ethical issues, and the effect of AEI on consumer trust and privacy. The results showed that although AEI improved user experiences by offering emotionally intelligent and tailored interactions, it also brought up serious issues with data security, privacy, and the possibility of emotional abuse. Additionally, the study revealed a significant deficiency in the existing regulatory structures, which had difficulty keeping up with the rapid advancements in technology. By giving a thorough examination of how AEI affected user habits and banking practices, the study added to the body of knowledge in the academic community. It also made recommendations for digital banking institutions on how to create strong policies and frameworks for the moral use of AI technology. This study contributed to the wider conversations on AI ethics and legal requirements while also deepening our understanding of AEI in the context of digital banking
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Artificial Emotional Intelligence; Customer Experience; Artificial Intelligence; Digital Bank; Internet Access; UCTD; SDG-9: Industry, innovation and infrastructure